Chapter Introduction - Łuszczyńska, Maria (Taylor & Francis, 2021)
With a focus on the case of Poland, where an aging population poses a crucial challenge for the state's social, family, and gerontological policy, this book explores ageing as a personal and social phenomenon, considering the ways in which the experience of ageing is shaped by younger generations' attitudes, government support policies, local initiatives undertaken help older people stay active, and the ways in which the elderly themselves understand their own mortality. Employing demographic, philosophical, legal, psychological, gerontological perspectives, it emphasises activities that can support older adults locally or nationwide and proposes the development of a social policy and social attitudes that can facilitate changes in the social perception of aging, together with a redistribution of resources for older adults. As such, it will appeal to scholars across the social sciences with interests in ageing and the lifecourse, as well as those who wish to support older adults with concrete solutions and familiarize themselves with the aging process from an individual and social perspective.